Analysis of Acceptance of Online Transportation Applications with the TAM Method - Yosi Afandi; Tri Lestariningsih (MultiTech Publisher, 2023)
The Grab application is one of the online transportation services in Indonesia. The Grab application also provides various services for consumer needs. From the various services provided by grab, it is necessary to conduct research to find out what variables affect the acceptance of the grab application. The method used is the TAM 3 method with the result that grab is accepted by consumers without being influenced by several, namely the Perceptions of External Control (PC) variable has no effect on the Behaviour Intention (BI) and Uses Behaviour (UB) variables, for the Subjective Norm (SN) variable has no effect on the Behaviour Intention (BI), Perceived Usefulnes (PU), and Uses Behaviour (UB) variables, while the Voluntariness (VOL) variable also has no effect on the Behaviour Intention (BI), Perceived Ease of Use (PEU), Perceived Usefulnes (PU), and Uses Behaviour (UB) variables.